Cannabinoid-Induced Hyperemesis: A Conundrum-From Clinical Recognition to Basic Science Mechanisms - Nissar A. Darmani (MDPI AG, 2010)
Cannabinoids are used clinically on a subacute basis as prophylactic agonist antiemetics for the prevention of nausea and vomiting caused by chemotherapeutics. Cannabinoids prevent vomiting by inhibition of release of emetic neurotransmitters via stimulation of presynaptic cannabinoid CB1 receptors. Cannabis-induced hyperemesis is a recently recognized syndrome associated with chronic cannabis use. It is characterized by repeated cyclical vomiting and learned compulsive hot water bathing behavior. Although considered rare, recent international publications of numerous case reports suggest the contrary. The syndrome appears to be a paradox and the pathophysiological mechanism(s) underlying the induced vomiting remains unknown. Although some traditional hypotheses have already been proposed, the present review critically explores the basic science of these explanations in the clinical setting and provides more current mechanisms for the induced hyperemesis. These encompass: (1) pharmacokinetic factors such as long half-life, chronic exposure, lipid solubility, individual variation in metabolism/excretion leading to accumulation of emetogenic cannabinoid metabolites, and/or cannabinoid withdrawal; and (2) pharmacodynamic factors including switching of the efficacy of Δ9-THC from partial agonist to antagonist, differential interaction of Δ9-THC with Gs and Gi signal transduction proteins, CB1 receptor desensitization or downregulation, alterations in tissue concentrations of endocannabinoid agonists/inverse agonists, Δ9-THC-induced mobilization of emetogenic metabolites of the arachidonic acid cascade, brainstem versus enteric actions of Δ9-THC, and/or hypothermic versus hyperthermic actions of Δ9-THC. In addition, human and animal findings suggest that chronic exposure to cannabis may not be a prerequisite for the induction of vomiting but is required for the intensity of emesis.